Impact of organic anion transporting polypeptide, P-glycoprotein, and breast cancer resistance protein transporters on observed tamoxifen and endoxifen concentration and adverse effects - Keller, Denise N; Medwid, Samantha J; Ross, Cameron D; Wigle, Theodore J; Kim, Richard B (Pharmacogenetics and genomics, 2023)
Drug transporters are important determinants of drug disposition and response. Tamoxifen is an antiestrogen for breast cancer therapy known for adverse drug reactions (ADRs). In this study, the involvement of OATP transporters in tamoxifen and endoxifen transport was studied in vitro while the impact of single nucleotide variation (SNV) in OATP and efflux transporters P-glycoprotein ( ABCB1 ) and Breast Cancer Resistance Protein ( ABCG2 ) on ADRs during tamoxifen therapy were assessed. Patients receiving tamoxifen for breast cancer, who were CYP2D6 normal metabolizers were enrolled ( n  = 296). Patients completed a survey that captured ADRs and a blood sample was collected. Tamoxifen and endoxifen plasma concentration were measured, while DNA was genotyped for SNVs in ABCB1, ABCG2, SLCO1A2, SLCO1B1 , and SLCO2B1 . HEK293T cells were used to determine the extent of OATP-mediated transport of tamoxifen and endoxifen. Common SNVs of ABCB1, ABCG2, SLCO1A2 , and SLCO1B1 were not associated with tamoxifen or endoxifen concentration. However, tamoxifen concentration was significantly higher in carriers of SLCO2B1 c.935G>A (129.8 ng/mL) compared to wildtype (114.9 ng/mL; P  = 0.036). Interestingly, subjects who carried SLCO1A2 c.38A>G reported significantly less dizziness ( P  = 0.016). In-vitro analysis demonstrated increased cellular accumulation of tamoxifen in cells overexpressing OATP1A2 and 1B1, but endoxifen uptake was not effected in OATP overexpressing cells. We showed that OATP1A2 , a transporter known to be expressed at the blood-brain barrier, is capable of tamoxifen transport. Additionally, OATP1A2 c.38A>G was associated with reduced ADRs. Taken together, our findings suggest genetic variation in OATP transporters may be an important predictor of tamoxifen ADRs.